Strengthening health care in Canada post-COVID-19 pandemic - Linda Rabeneck; Chris McCabe; Mark Dobrow; Arlinda Ruco; Melissa Andrew; Sabrina Wong; Sharon Straus; Lawrence Paszat; Lisa Richardson; Chris Simpson; Andrew Boozary (FACETS, 2023)
The purpose of this policy briefing is to examine our health care systems through the lens of the COVID-19 pandemic and identify how we can strengthen health care in Canada post-pandemic. The COVID-19 pandemic has provided compelling evidence that substantive changes to our health care systems are needed. Specifically, the pandemic has emphasized structural inequities on a broad scale within Canadian society. These include systemic racial and socioeconomic inequities that must be addressed broadly, including in the delivery of health care. We make recommendations about what we can do to emerge stronger from the pandemic. While these recommendations are not novel, how they are framed and contextualized differs because of the problems in our health care system that have been highlighted and exacerbated by the pandemic.The evidence is clear that socioeconomic circumstances, intergenerational trauma, adverse early life experiences, and educational opportunities are critical factors when it comes to health over the life course. Given the problems in the delivery of health care that the pandemic has revealed, we need a different approach. How health care was organized prior to the COVID-19 pandemic did not produce what people wanted and needed in terms of health care and outcomes. How do we emerge from COVID-19 with an effective, equitable, and resilient health care system for all Canadians? To address health inequities and emerge from the pandemic with strengthened health care in Canada, we must consider how Amartya Sen's capabilities framework on social well-being can be operationalized to achieve better health care and health outcomes. Specifically, we address the need to: strengthen primary care and improve access to primary care; utilize a community-embedded approach to care; and implement better integration across the care continuum, including integration between primary care and public health. Coherent governance and leadership that are charged with realizing benefits through collaboration will maximize outcomes and promote sustainability. Only when we provide access to high-quality culturally competent care that is centered around the individual and their needs will we be able to make true headway in addressing these long-standing health inequities.